Developmental Characteristics of Disparate Bimanual Movement Skills in Typically Developing Children. Issue 1 (2nd January 2018) - Rudisch, Julian; Butler, Jenny; Izadi, Hooshang; Birtles, Deirdre; Green, Dido
ABSTRACT: Mastery of many tasks in daily life requires role differentiated bimanual hand use with high spatiotemporal cooperation and minimal interference. The authors investigated developmental changes in the performance of a disparate bimanual movement task requiring sequenced movements. Age groups were attributed to changes in CNS structures critical for bimanual control such as the corpus callosum (CC) and the prefrontal cortex; young children (5–6 years old), older children (7–9 years old), and adolescents (10–16 years old). Results show qualitative changes in spatiotemporal sequencing between the young and older children which typically marks a phase of distinct reduction of growth and myelination of the CC. Results show qualitative changes in spatiotemporal sequencing between the young and older children, which coincides with distinct changes in the growth rate and myelination of the CC. The results further support the hypothesis that CC maturation plays an important role in the development of bimanual skills.